Analysis Of Accounting Information For The Purchase Of Raw Materials And Inventory Of Raw Materials : Analisis Sistem Informasi Akuntansi Pembelian Bahan Baku Dan Persediaan Bahan Baku Pada Perusahaan Arang - Ismul Wahyu Riski; Imelda Dian Rahmawati (Academia Open, 2021)
This research was conducted with the aim of proving the implementation of the accounting system for raw material inventories and purchasing of raw materials at the charcoal company PT. Karang Pilang Agung, in addition to monitoring problems that occur in accounting system at PT. Karang Pilang Agung, and to analyze whether the accounting information system for purchases, raw material inventory applied by PT. Karang Pilang Agung is in accordance with the accounting information system theory. In this research, qualitative approach was used. The data methods used were interviews, documentation, and observation. The interview method is used to find more in-depth information with the stage of giving questions to the general section and the expert section. The documentation method is used to corroborate the data in the triangulation process. The observation method is used to collect data with information notes during the research directly in the factory. The data analysis technique used is qualitative with the triangulation method. The results showed that the accounting information system for raw material inventory applied at PT. Karang Pilang Agung has been going well. This is evidenced by the selection of each supplier, and checking the quantity and specifications of raw materials or goods that come by involving various functions with their respective duties and responsibilities and have been equipped with documents that can be accounted for. The results of the research on the accounting information system for the purchase of raw materials are also going very well, with the Quality Control (QC) section and also each new supplier will be selected according to company criteria.